Effect of N-cadherin on Chondrogenic Differentiation of Bone Marrow-Derived Mesenchymal Stem Cells through Wnt Signaling Pathway - Feng, Qu; Xuezhen, Shen; Haipeng, Li; Jingbin, Zhou; Bangtuo, Yuan; Chunbao, Li; Wei, Qi; Yujie, Liu; Mingzhu, Zhang (Cellular and Molecular Biology, 2022)
This study aimed to compare and analyze the effect of N-cadherin on chondrogenic differentiation of bone marrow-derived mesenchymal stem cells (BMSCs) and to explore the related mechanism, so as to provide a novel theoretical basis for the clinical work of articular cartilage injury regeneration and repair. For this purpose, the experimental animals were clean grade SD rats (aged 5-6 weeks, weighing 180-250g). Alcian blue staining was carried out to observe the induced chondrogenesis following N-cadherin inhibition. The specific role of N-cadherin in the Wnt signaling pathway and chondrogenic differentiation of BMSCs was detected by Western blot; while the effect of N-cadherin on the molecular level changes of β-catenin in the cytoplasm was evaluated by fluorescence quantitative real-time PCR (qRT-PCR). In addition, immunoprecipitation (IP) was used for the verification of the interaction between N-cadherin and β-catenin. Results showed that under the light microscope, 90% of the BMSCs at the third generation, 90% of the cells were fused. Alcian blue staining showed that the green staining area in the BMP2 induction group was large and dense, while that in the N-cadherin inhibition group and blank control group was small and sparse. Western blot revealed that N-cadherin and SOX9 were significantly developed in the BMP2 induction group, but Wnt3a was not significantly developed. While in the N-cadherin inhibition group, the development of Wnt3a was obvious, yet without evident development of N-cadherin and SOX9. The qRT-PCR indicated that the relative mRNA expression of Wnt3a was significantly increased in the N-cadherin inhibition group (P<0.05). However, no obvious difference was observed in the mRNA expression of β-catenin between the BMP2 induction group and the N-cadherin inhibition group (P>0.05). Western blot indicated that in the BMP2 induction group; there existed the development of β-catenin, significant development of phos-GSK-3β and total GSK-3β, but no obvious development of Wnt3a. In the N-cadherin inhibition group, there was significantly enhanced development of Wnt3a and β-catenin than that before, blurred development of phos-GSK-3β than that before, and also obvious development of total GSK-3β with little change from before. N-cadherin promoted the expression of β-catenin mostly in the cell membrane, but only a few in the cytoplasm and nucleus. Additionally, verification by IP showed that N-cadherin and β-catenin were developed on N-cadherin and β-catenin bands, suggesting an interaction between N-cadherin and β-catenin. According to these results, N-cadherin can ultimately promote chondrogenic differentiation of BMSCs by inhibiting the Wnt signaling pathway.